Influence of Instantaneous Compression on Recognition of Speech in Noise with Temporal Dips - Rasetshwane, Daniel M.; Raybine, David A.; Kopun, Judy G.; Gorga, Michael P.; Neely, Stephen T. (Journal of the American Academy of Audiology, 2019)
In listening environments with background noise that fluctuates in level, listeners with normal hearing can “glimpse” speech during dips in the noise, resulting in better speech recognition in fluctuating noise than in steady noise at the same overall level (referred to as masking release). Listeners with sensorineural hearing loss show less masking release. Amplification can improve masking release but not to the same extent that it does for listeners with normal hearing.The purpose of this study was to compare masking release for listeners with sensorineural hearing loss obtained with an experimental hearing-aid signal-processing algorithm with instantaneous compression (referred to as a suppression hearing aid, SHA) to masking release obtained with fast compression. The suppression hearing aid mimics effects of normal cochlear suppression, i.e., the reduction in the response to one sound by the simultaneous presentation of another sound.A within-participant design with repeated measures across test conditions was used.Participants included 29 adults with mild-to-moderate sensorineural hearing loss and 21 adults with normal hearing.Participants with sensorineural hearing loss were fitted with simulators for SHA and a generic hearing aid (GHA) with fast (but not instantaneous) compression (5 ms attack and 50 ms release times) and no suppression. Gain was prescribed using either an experimental method based on categorical loudness scaling (CLS) or the Desired Sensation Level (DSL) algorithm version 5a, resulting in a total of four processing conditions: CLS-GHA, CLS-SHA, DSL-GHA, and DSL-SHA.All participants listened to consonant-vowel-consonant nonwords in the presence of temporally-modulated and steady noise. An adaptive-tracking procedure was used to determine the signal-to-noise ratio required to obtain 29% and 71% correct. Measurements were made with amplification for participants with sensorineural hearing loss and without amplification for participants with normal hearing.Repeated-measures analysis of variance was used to determine the influence of within-participant factors of noise type and, for participants with sensorineural hearing loss, processing condition on masking release. Pearson correlational analysis was used to assess the effect of age on masking release for participants with sensorineural hearing loss.Statistically significant masking release was observed for listeners with sensorineural hearing loss for 29% correct, but not for 71% correct. However, the amount of masking release was less than masking release for participants with normal hearing. There were no significant differences among the amplification conditions for participants with sensorineural hearing loss.The results suggest that amplification with either instantaneous or fast compression resulted in similar masking release for listeners with sensorineural hearing loss. However, the masking release was less for participants with hearing loss than it was for those with normal hearing.
Keywords: aided audibility index; hearing aids; instantaneous compression; masking release